Reasons Influencing PrEP continuity among Key and Priority Populations in Tabora region, Tanzania. A cross-sectional study. - Mrisho, Adam; Rutatinisibwa, Honoratha; Msalale, George; Shemtandulo, Ramadhani; Mturi, Benson; Ambonisye, Steven; Rumisha, AbelaAbele; Ayoub, Mohamed; Shirima, Charles; Mauka, Wilhellmuss; Atuhaire, Shallon; Maziku, Evaline; et al. (Student’s Journal of Health Research Africa, 2022)
Background: In Tabora, PrEP continuity 6 months after among newly enrolled among Key and Priority Population (KPP) is low at 47%. However, information on reasons influencing to PrEP continuity in KPP in Tabora is limited. We report study findings from nine (9) health facilities (HFs) in the Tabora region. Methodology: This was a cross-sectional survey, deployed both quantitative and qualitative methods. 425 current or previous PrEP beneficiaries started PrEP between July 2020 to January 2021 were administered with a structured questionnaire, whereby 157 participants were purposively selected for 18 focused group discussions (FGDs). Recruitment of study participants carried between February to April 2022. Results: A total of 425 KPPs, aged 15-70 years with average 30 years, the majority 288(58%) were FSWs, the proportion of interruption was 25(20.5%). Reported reasons for PrEP interruptions, (57%) were due to drug side effects and the least was migration (3%). There was an association between interruptions and clients’ age (P<0.05), area of service offered (P=0.010.) and being knowledgeable about PrEP: (P<0.05). There is significant relationship between awareness and PrEP interruptions, though in proportions of those aware and had interruptions was at 33%. Conclusion: Drugs side effects, misconception, stigma, pill burden and migration were cited among influencing reasons for PrEP interruptions. Recommendations: Interventional study recommended to explore on the reasons cited for PrEP discontinuity in reaching PrEP goals in prevention services.